2009
DOI: 10.1177/0020764008095930
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Obese Persons Before Starting Complex Group Weight-Reduction Programme

Abstract: Depression often accompanies obesity. The depression levels increased in morbidly obese persons in comparison to moderately obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…The results were also comparable when the criterion of identity was gender. Therefore, it seems that baseline depression levels did not disturb the weight reduction, although as observed previously, the depression level increased with severe obesity [17,27].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The results were also comparable when the criterion of identity was gender. Therefore, it seems that baseline depression levels did not disturb the weight reduction, although as observed previously, the depression level increased with severe obesity [17,27].…”
Section: Discussionsupporting
confidence: 68%
“…Magdalena Olszanecka-Glinianowicz 1 system activation [7,8], disturbance of neurotransmitter secretion [9][10][11][12][13] and immune activation [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For the background group, at baseline, 26% of patients had BDI scores in the normal range (0-9), 38% in the mild depression range (10)(11)(12)(13)(14)(15)(16)(17)(18), 26% in the moderate depression range (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and 10% in the severe depression range (30+). The mean BDI score of this background group falls within the mild range (10-18) of depressive symptoms.…”
Section: Range Of Bdi Scoresmentioning
confidence: 99%
“…Several studies have reported little or no depressive symptoms in obese individuals [18,19] and even lower levels of depression in obese middle-aged men [20,21]. There are several studies indicating that as BMI increases, so do the depression levels [6,22]; this relationship has also been suggested to be a U-shaped association from underweight to obese class III [23]. Zhao et al [24] reported gender differences; specifically that in women, depression was increased when underweight, overweight, and obese class I only compared to normal weight and in men when underweight and obese class III only.…”
Section: Introductionmentioning
confidence: 99%
“…Studies previously published indicate that levels of depressive symptoms increase proportionally as BMI increases (10,22). It is well known that after weight loss, either with bariatric surgery or any other type of intervention, depressive symptoms improve (23,24).…”
Section: Discussionmentioning
confidence: 99%